Preventing the development of severe COVID-19 by modifying immunothrombosis - Morris, Gerwyn (Life Sci, 2021)
BACKGROUND: COVID-19-associated acute respiratory distress syndrome (ARDS) is associated with significant morbidity and high levels of mortality. This paper describes the processes involved in the pathophysiology of COVID-19 from the initial infection and subsequent destruction of type II alveolar epithelial cells by SARS-CoV-2 and culminating in the development of ARDS. MAIN BODY: The activation of alveolar cells and alveolar macrophages leads to the release of large quantities of proinflammatory cytokines and chemokines and their translocation into the pulmonary vasculature. The presence of these inflammatory mediators in the vascular compartment leads to the activation of vascular endothelial cells platelets and neutrophils and the subsequent formation of platelet neutrophil complexes. These complexes in concert with activated endothelial cells interact to create a state of immunothrombosis. The consequence of immunothrombosis include hypercoagulation, accelerating inflammation, fibrin deposition, migration of neutrophil extracellular traps (NETs) producing neutrophils into the alveolar apace, activation of the NLRP3 inflammazome, increased alveolar macrophage destruction and massive tissue damage by pyroptosis and necroptosis Therapeutic combinations aimed at ameliorating immunothrombosis and preventing the development of severe COVID-19 are discussed in detail.